Use of Information and Communication Technologies (ICTs) in Youth and Adult Education in a school in Castanhal, Pará – Brazil (Research, Society and Development, 2024)
This article discusses the contributions of Information and Communication Technologies to the teaching of students in a public school in Castanhal, in the state of Pará – Brazil. For this, a brief contextualization of the historicity of Youth and Adult Education is made and the use of ICTs in this teaching modality is addressed. Objectives: to present the theoretical contributions of ICTs in the teaching-learning process of EJA in a school in the municipality of Castanhal/PA. Methodology: Narrative Review of Literature with a qualitative approach and descriptive nature. Results: 21 publications were used to compose the theoretical contribution of the research, through database queries of Public Repositories, Scientific Electronic Library Online - Scielo and Capes/SUCUPIRA Portal. Final Considerations: with regard to the teaching of EJA and the use of ICTs in the public school of Castanhal/PA, it is important for teachers, coordination and direction to be aligned on the implementation or even the restoration of the use of technologies in their classes, as a methodology to make teaching more flexible, guaranteeing students the realization of rights to be literate, obtaining personal and social development.